Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1016/j.virol.2003.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of transcription of the proapoptotic gene BNip3 in cultured astrocytes by murine coronavirus infection

Abstract: Murine coronavirus mouse hepatitis virus (MHV) causes encephalitis and demyelination in the central nervous system of susceptible rodents. Astrocytes are the major target for MHV persistence. However, the mechanisms by which astrocytes survive MHV infection and permit viral persistence are not known. Here we performed DNA microarray analysis on differential gene expression in astrocyte DBT cells by MHV infection and found that the mRNA of the proapoptotic gene BNip3 was significantly decreased following MHV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Some of the genes induced in astrocytes by TNF-α or IL-1β described in this work were up-regulated by HIV-1 or SIV in vivo (Table 1). Other microarray analyses have shown that exposure of astrocytes in culture to different viruses (Cai et al 2003; Radhakrishnan et al 2003; Aravalli et al 2006; Rubio and Sanz-Rodriguez 2007), conditions of hypoxia (Mense et al 2006), and environmental toxins (Everall et al 2005; Mense et al 2006; Sengupta et al 2007) can all significantly alter gene expression profiles of these cells. While the results of such studies cannot be directly extrapolated to pathogenic situations in HIV-1-infected brains, they clearly indicate that astrocytes are highly reactive cells and that their physiological functions can be profoundly altered by contact with a wide variety of natural and pathogenic stimuli, including HIV-1.…”
Section: Other Studies In Astrocytes Using Functional Genomics With Pmentioning
confidence: 99%
“…Some of the genes induced in astrocytes by TNF-α or IL-1β described in this work were up-regulated by HIV-1 or SIV in vivo (Table 1). Other microarray analyses have shown that exposure of astrocytes in culture to different viruses (Cai et al 2003; Radhakrishnan et al 2003; Aravalli et al 2006; Rubio and Sanz-Rodriguez 2007), conditions of hypoxia (Mense et al 2006), and environmental toxins (Everall et al 2005; Mense et al 2006; Sengupta et al 2007) can all significantly alter gene expression profiles of these cells. While the results of such studies cannot be directly extrapolated to pathogenic situations in HIV-1-infected brains, they clearly indicate that astrocytes are highly reactive cells and that their physiological functions can be profoundly altered by contact with a wide variety of natural and pathogenic stimuli, including HIV-1.…”
Section: Other Studies In Astrocytes Using Functional Genomics With Pmentioning
confidence: 99%
“…First, we determined the BNip3 promoter activity by using the luciferase reporter assay . We expressed Egr-1 protein transiently in DBT cells by cotransfecting pBS-CMV-Egr-1, which contains the Egr-1 ORF under the control of a CMV promoter, and pGL3-BNip3 reporter plasmid (Bruick, 2000;Cai et al, 2003). After 20 h post-transfection, cell lysates were harvested and luciferase activity determined.…”
Section: Over-expression Of Egr-1 Repressed Bnip3 Promoter Activitymentioning
confidence: 99%
“…However, the mechanism of establishment of coronavirus persistence has not been yet well understood. Recently, the down-regulation of the pro-apoptotic protein BNip-3 was found in MHV-infected DBT cells by DNA microarray methodologies [2]. In MHV-infected cells, BNip3 levels were significantly decreased at the transcriptional level, and this down-regulation was mediated by the fusion between the viral envelope and the cell membrane.…”
mentioning
confidence: 99%